A Retrospective Observational Study of Combination Treatment of Thread Lift and High-intensity Focused Ultrasound for Facial Aging - Yu-Ching Weng, MD; Chia-Hsien Hsieh, MD; Ben Chung-Pin Liang, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Current literature lacks guidelines on the optimal treatment number of threads for specific indications and provides limited evidence on the efficacy of combining thread lift with other materials or devices for synergistic effects. Methods:. This study evaluates the therapeutic outcomes of combining thread lift therapy with high-intensity focused ultrasound. Fifty-eight participants, divided into 2 groups of 29, received 3 treatments, each involving unilateral insertion of four 17-cm-long barbed Miracle threads and 200 lines of ultrasound therapy with a 4.5-mm UTIMS probe on the middle and lower face. Results:. Wilcoxon signed-rank tests showed significant improvements in physician-evaluated Merz aesthetic scores between the second and first visits (Z = −6.057, P < 0.01), the third and second visits (Z = −5.112, P < 0.01), and between the photograph session and both the third (Z = −5.425, P < 0.01) and first visits cumulatively (Z = −4.943, P < 0.01). Additionally, Wilcoxon 2-tailed signed-rank test revealed significant reductions in jowl fat pad distance across treatment sessions. Conclusions:. The treatment sequence did not affect facial lifting outcomes, and 3 sessions of combined thread lift and high-intensity focused ultrasound therapy sustained effects in partial participants.